Energy and Exergy Analysis of Chest Freezer Using R134a and R290 as Working Fluids Based on Experimental Data - Pramudantoro, Triaji Pangripto; Muliawan, Rizki; Nuriyadi, Muhammad; Hidayat, Syarif; Tohir, Toto; Sulaimon, Shodiya (Jurnal Internasional Penelitian Teknologi Terapan, 2024)
Although R134a has a very high global warming (GWP) effect, it is still used as a refrigerant in chest freezers. As an alternative to R134a is R290 which has a very low GWP value, which is only 3. Therefore, it is expected that there will be no more chest freezers using R134a and replaced with R290, soon. Thermodynamic studies need to be conducted to see the advantages and disadvantages of the two refrigerants based on experimental data. In this study, a chest freezer which was originally manufactured for R134a with a charging mass of 150 g was used as a test object. Experimental data of the chest freezer using R290 was taken after testing with R134a was completed. Experimentally, the cabin temperatures of the chest freezer using R134a and R290 are -20.5oC and -35.7oC, respectively, and the input power are 264 W and 176 W, respectively. Total irreversibility on the four main components of the chest freezer using R134a is greater than using R290, namely 184.4 W and 107.0 W, respectively. This means that the use of R290 as a working fluid in the chest freezer is more efficient. There are at least three advantages of replacing R134a with R290, namely reducing greenhouse gas emissions because R290's GWP is much smaller than R134a, lower cabin temperature, and decreasing the input power of the chest freezer.